2010
DOI: 10.1159/000288701
|View full text |Cite
|
Sign up to set email alerts
|

Vagotomy Suppresses Body Weight Gain in a Rat Model of Gastric Banding

Abstract: Background: The aim of this study was to evaluate the effect of vagotomy on body weight changes after gastric banding. Methods: Rats were divided into a sham-operated group (n = 10), a vagotomy alone group (n = 10), a gastric banding alone group (n = 10) and a gastric banding + vagotomy group (n = 10). All groups were given a liquid diet for 5 days after surgery and then given free access to chow. Their body weight was measured through postoperative day (POD) 14, and caloric intake and nitrogen balance were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Truncal vagotomy also produced transient decreases in spontaneous glutamate release, glutamate release probability, and the number of primary afferent inputs [ 30 ]. Interestingly, several studies report that vagotomy reduces food intake and body weight [ 52 – 54 ]. Moreover, recent studies indicate that signals carried by vagal afferents from the GI tract contribute to the early RYGB-induced body weight loss and reduction of food intake [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Truncal vagotomy also produced transient decreases in spontaneous glutamate release, glutamate release probability, and the number of primary afferent inputs [ 30 ]. Interestingly, several studies report that vagotomy reduces food intake and body weight [ 52 – 54 ]. Moreover, recent studies indicate that signals carried by vagal afferents from the GI tract contribute to the early RYGB-induced body weight loss and reduction of food intake [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…While this method is very crude, it did reveal striking disturbances in food intake. However, the results were inconsistent, with some studies reporting a decrease in weight and others reporting no difference or even an increase in weight . Furthermore, a vagotomy also reduces gastric relaxation, motility and secretions, that is, acid and gastrin, all making a role for the vagus in the control of food intake hard to identify.…”
Section: The Importance Of the Vagus In Food Intake Regulationmentioning
confidence: 99%
“…Historically, procedures associated with greater manipulation of the vagus nerve have included esophagectomies, gastrectomies, RYGB, and Billroth configurations; they all reroute the foregut anatomy [11]. Interestingly enough, upon review of other reported LAGB studies, these studies have investigated long-term weight regulating effects of vagotomy when performed in conjunction with gastric banding, however, not specifically hypoglycemia [1215]. …”
Section: Discussionmentioning
confidence: 99%